Can pre-treatment inflammatory biomarker levels predict the response of tocilizumab therapy in COVID-19 patients? - Mehmet Nur Kaya; Duygu Tecer; Muhammet Çınar; Fahrettin Bıçakcı; Emre Tekgöz; Seda Çolak; Sedat Yılmaz (Gülhane Tıp Dergisi, 2023)

(untitled)
Aims:The results of randomized clinical trials evaluating the effects of tocilizumab in patients with patients are inconsistent. We aimed to investigate the reliability of pre-treatment levels of prognostic nutritional index (PNI), C-reactive protein (CRP)/albumin ratio (CAR), systemic immune-inflammatory index (SII), interleukin-6 (IL-6), and lactate dehydrogenase (LDH) as treatment response biomarkers in hospitalized coronavirus disease-2019 (COVID-19) patients who were administered tocilizumab.Methods:Adult patients hospitalized for COVID-19 confirmed by severe acute respiratory syndrome-coronavirus-2 polymerase chain reaction and administered tocilizumab because of rapid clinical worsening despite receiving standard care were retrospectively included. Patients who received steroids, anakinra, or IVIG before tocilizumab and had missing data were excluded. Treatment effectiveness was evaluated with the improvement in the clinical status on an eight-category ordinal scale at 28 days of tocilizumab administration.Results:One hundred and thirty-three COVID-19 patients with a mean age of 62.64±13.66 years and consisting of 93 (69.9%) males were included. At 28 days of tocilizumab administration, 99 (74.4%) patients improved. Improved patients after tocilizumab treatment had significantly lower IL-6, LDH, SII, CAR, and higher PNI. To predict the effectiveness of tocilizumab, IL-6 had the highest area under the curve (AUC) value (AUC=0.782), followed by LDH (AUC=0.761), PNI (AUC=0.696), SII (AUC=0.671), CAR (AUC=0.682), and CRP (AUC=0.643). The cut-off level was 143.12 pg/mL for IL-6 (sensitivity=84.85%, specificity=64.71%), 460U/L for LDH (sensitivity=71.72%, specificity=73.75%), 31.35 for PNI (sensitivity=79.80%, specificity=55.88%), 3895.92 for SII (sensitivity=90.91%, specificity=47.06%), and 61.15 for CAR (sensitivity=67.68%, specificity=61.76%).Conclusions:In COVID-19 patients with clinically worsening disease, the administration of tocilizumab in the early stage of the hyperinflammatory state may improve the prognosis. Pre-treatment inflammatory biomarker levels may predict tocilizumab response.